UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI METODE QUESTIONING DENGAN TEKNIK CARD SHORT PADA MATERI NEGARA-NEGARA ASEAN - Tani Isnaini (MEDIA DIDAKTIKA, 2023)
The purpose of the study was to apply the method of questioning with a short card techniques in order to improve the learning outcomes of Civics. The research subjects were the sixth graders of the second state elementary school of Dumpiagung, Kembangbahu District, Lamongan. The study was designed in the Classroom Action Research (PTK). The result showed that the application of the method of questioning with a short card techniques could improve the learning outcomes of Civics. This is evident from the average value of second-grade students in the first cycle was 62.5 with a 45% passing rate. The number of students who pass were 9 students from 20 students. The average value of the second cycle test result was 70.5 to 60% the percentage of completeness. The number of students who pass were 12 students from 20 students.